2004
DOI: 10.1242/jcs.00847
|View full text |Cite
|
Sign up to set email alerts
|

N-RAP scaffolds I-Z-I assembly during myofibrillogenesis in cultured chick cardiomyocytes

Abstract: N-RAP is a muscle-specific protein with an N-terminal LIM domain (LIM), C-terminal actin-binding super repeats homologous to nebulin (SR) and nebulin-related simple repeats (IB) in between the two. Based on biochemical data, immunofluorescence analysis of cultured embryonic chick cardiomyocytes and the targeting and phenotypic effects of these individual GFP-tagged regions of N-RAP, we proposed a novel model for the initiation of myofibril assembly in which N-RAP organizes α-actinin and actin into the premyofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 38 publications
6
44
0
Order By: Relevance
“…Digital images were obtained using Zeiss LSM software. Morphometric analysis was performed using Image J software as previously described [24,25].…”
Section: Immunostaining and Confocal Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Digital images were obtained using Zeiss LSM software. Morphometric analysis was performed using Image J software as previously described [24,25].…”
Section: Immunostaining and Confocal Microscopymentioning
confidence: 99%
“…Therefore, conclusions regarding the effects of Krp1 knockdown on myofibril assembly can only be made based on quantitative analysis from many cells. The morphometric analysis of striated α-actinin provides a reproducible measure of Zline assembly (figure 5B) [24][25][26], while assignment of cardiomyocytes according to patterns of α-actinin organization yields additional information concerning the organization of this protein at different times ( figure 7). Using these quantitative assays, we examined the effects of Krp1 knockdown on accumulation of mature Z-lines and tracked the accumulation of normally low abundance assembly and disassembly intermediates in the cardiomyocyte population.…”
Section: Krp1 Promotes Lateral Fusion Of Myofibril Assembly Intermedimentioning
confidence: 99%
See 1 more Smart Citation
“…Although subcellular localization and biochemical copurification from adult muscles suggested that N-RAP may link the ends of myofibrils to membrane-associated protein complexes, studies in cultured embryonic cardiomyocytes have implicated N-RAP in myofibril assembly (Carroll and Horowits, 2000;Carroll et al, 2001Carroll et al, , 2004Lu et al, 2003). These studies showed that N-RAP localizes with the earliest myofibril precursors that originate near the membrane (Carroll and Horowits, 2000;Lu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in cell culture have established that sarcomere assembly is a stepwise program that initiates at the basal surface of the sarcolemma, at which sarcomere precursors are tethered before their transition to mature striated myofibrils (Rhee et al, 1994;Dabiri et al, 1997;Carroll et al, 2004). Thus, sarcolemmal adhesions appear to contribute to sarcomerogenesis by providing a scaffold for assembly.…”
Section: The Z-disk As a Focal Point For Force Propagationmentioning
confidence: 99%